This problem states to find the Laplace Transform to solve the given initial value problem: $\displaystyle y'' - 2 y' + 2 y = cost; y(0) = 1, y'(0) = 0 $ $\displaystyle y'' - 2 y' + 2 y = e^{-t}; y(0) = 2, y'(0) = 1 $
Follow Math Help Forum on Facebook and Google+
Originally Posted by fudawala This problem states to find the Laplace Transform to solve the given initial value problem: $\displaystyle y'' - 2 y' + 2 y = cost; y(0) = 1, y'(0) = 0 $ $\displaystyle y'' - 2 y' + 2 y = e^{-t}; y(0) = 2, y'(0) = 1 $ How about you type out what you tried. And I correct you if necessary.
View Tag Cloud